Agronomy Performance and Resistance of Shallots against Fusarium Wilt Disease under Various Salicylic Acid Treatments - Khotimah, Khusnul (Talenta Publisher, 2022)
This research aims to know the agronomic character and resistance of shallots against fusarium wilt disease under various salicylic acid treatments. This research was conducted in a greenhouse using a completely randomized design with one factor, namely the treatment of salicylic acid concentrations (0 ppm, 15 ppm, 20 ppm, and 25 ppm) with 3 replications. Each treatment was inoculated with Fusarium acutatum inoculum (106 conidia ml-1 distilled water) except for the negative control, without being inoculated with Fusarium acutatum inoculum. The materials used included shallot bulbs of the Tajuk variety, synthetic salicylic acid, Fusarium acutatum inoculum. Variables of observation of agronomic characters include; plant height, number of leaves, fresh tuber weight while the disease component variables include; incubation period, and disease incidence. The data obtained were analyzed by analysis of variance (ANOVA) with a significance level of 95%, then the DMRT test (95%) was carried out to determine the differences between treatments. The results of the analysis of variance showed that there was a significant difference between the 0 ppm treatment (control) and the 15, 20, and 25 ppm treatment on the characters of plant height, fresh weight, and disease incidence. Meanwhile for the character of the number of leaves and incubation period there was no significant difference between the control and salicylic acid treatment. Salicylic acid treatment at a concentration of 15 ppm showed the highest plant height (34.26 cm), the highest number of leaves (24.46 strands), the highest fresh tuber weight (6.30 g), and the least disease incidence (14.55%).